Biogenic treatment improves the durability and remediates the cracks of concrete structures - Achal, V.; Mukherjee, Abhijit; Reddy, M. (Elsevier BV, 2013)
Microbially induced calcium carbonate precipitation is a naturally occurring biological process that has various applications in remediation and restoration of range of building materials. In the present study the role of bacteria Bacillus sp. on the durability properties and remediation of cracks in cementitious structures were studied. ‘‘Biocement’’ induced by a Bacillus sp. lead to more than 50% reduction in the porosity of mortar specimens, while chloride permeability of concrete changed from ‘‘moderate’’ to ‘‘very low’’ as indicated by rapid chloride permeability test. The bacteria successfully healed the simulated cracks of depths including 27.2 mm in cement mortars with increase in the compressive strength as high as 40% of that of control. The results clearly showed microbially induced calcium carbonate precipitation can be applied for various building materials for remediation of cracks and enhancement of durability.